Ejercicios orofaciales y el lenguaje oral en niños de 4 a 5 años de la Escuela de Educación Básica Miguel Riofrío de la ciudad de Loja en el periodo 2023-2024 - Guillen Chalco, Josue Israel (2024)
Oral language is considered the first form of communication used by human beings, which allows interaction and the development of cognitive skills essential for one personal and social performance, in addition, oral language facilitates problem-solving and decision-making, as it makes it possible the exchange of ideas and perspectives, in this way its acquisition in childhood is a vital process that is closely linked to cognitive development. Therefore, the present research aimed to determine how orofacial exercises strengthen the oral language of children from 4 to 5 years old of the Miguel Riofrío Basic Education School in Loja City in the period 2023-2024; the research was carried out under a mixed approach, with a non-experimental design, descriptive scope and by means of the methods: inductive-deductive, analytical-synthetic. To obtain information on the variables, the oral language test Navarre Revised (PLON-R) was used as an instrument, which was applied to twenty-three children from four to five years old, obtaining as a result that 34.78% were in a level of delay, those who presented difficulties because they did not articulate phonemes in an adequate way, a reduced vocabulary, shyness when speaking, little understanding and expression of words, thus a guide of activities was designed called the guide "Exploring and learning in oral language". It is concluded that the orofacial exercises improve the linguistic skills of children, promoting an adequate articulation of phonemes, an increase of the lexicon and facilitating the comprehension and expression of oral language, which provides a clear and fluent communication. Key words: Oral language, initial, orofacial, linguistics, semantics, pragmatics.